Scientific School Image Development of a University Based on the System of Public Relations - Turanina, Neonila A.; Murashko, Olga Y.; Kulyupina, Galina A.; Zamanova, Irina F.; Perepelkin, Igor N. (International Journal of Criminology and Sociology, 2022)
The article considers the problem of educational institution promotion in the external socio-cultural environment via innovative management, in particular, the Public relations system. The solution to this problem is important in terms of fierce competition in the educational services market. The authors draw attention to the fact that scientific schools as unique associations of university science representatives can be considered as one of the effective elements of the university image policy development. They outlined the primary tasks of the university scientific school positive image development in the public relations system, PR tools are highlighted in the internal university environment and in the external sphere of the university, where the following segments are considered as the target audience: the scientific community outside the university, potential employers of university graduates, and the population represented by potential applicants and their parents.